2018
DOI: 10.1371/journal.pone.0198566
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between left main and left anterior descending arteries bifurcation angle and coronary artery calcium score in chronic kidney disease: A 3-dimensional analysis of coronary computed tomography

Abstract: BackgroundA high coronary artery calcium score (CACS) predicts a poor prognosis in patients with coronary artery disease. We examined the relationship between the bifurcation angle and the CACS of the left main (LM) and left anterior descending (LAD) arteries in patients suffering from chronic kidney disease (CKD).MethodsWe analyzed the data of 121 patients who underwent coronary computed tomography between October 2014 and June 2015 and whose estimated glomerular filtration rate (eGFR) was <60 ml/min/1.73 m2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Because vessels with advanced atherosclerosis also may show a complex morphology due to curvature or tortuosity in the actual clinical setting, measurement of the bifurcation would optimally be better performed by three-dimensional analysis. However, similar to our experience in previous studies [ 9 , 18 , 19 , 25 ], it was quite difficult to assess the bifurcation angle by three-dimensional analysis. Moreover, complex vessel morphology may affect blood flow leading to paradoxical FFR CT changes.…”
Section: Limitationssupporting
confidence: 58%
See 1 more Smart Citation
“…Because vessels with advanced atherosclerosis also may show a complex morphology due to curvature or tortuosity in the actual clinical setting, measurement of the bifurcation would optimally be better performed by three-dimensional analysis. However, similar to our experience in previous studies [ 9 , 18 , 19 , 25 ], it was quite difficult to assess the bifurcation angle by three-dimensional analysis. Moreover, complex vessel morphology may affect blood flow leading to paradoxical FFR CT changes.…”
Section: Limitationssupporting
confidence: 58%
“…As in previous studies [ 18 , 19 ], each bifurcation angle was measured as the crossing angle between the center lines of the left main trunk and each coronary artery (LAD or LCX) on the three-dimensional volume-rendered image of the coronary artery tree. For the left coronary artery bifurcation angle both LAD angle and LCX were determined by assessing the crossing line with the left main trunk (Supplementary Figure 2 : center panel).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of high-risk (71±19° vs. 55±19°) and non-calcified plaques (74±20° vs. 50±14°) in the proximal MV was associated with wider Angle B values [ 46 ]. A narrower Angle A in the LMCA in patients with chronic kidney disease was likely to present with more calcified lesions [ 20 ]. Another CCTA study revealed that angle change due to the cardiac motion was more prominent in the Angle A (LMCA-LCX angle) compared to the Angle C (LMCA-LAD angle) [ 33 ].…”
Section: Review and Discussionmentioning
confidence: 99%
“…However, two modes of defining the BA related to the MV and SB have been reported to date, which has led to some confusion in the understanding of the results of each analysis. Although the angle between the centerline of the proximal MV and the SB (BA-α, complementary angle of Angle A) has been defined as the BA in several reports [14][15][16][17][18][19][20] (Fig 2B ), Angle B has been considered as the more accepted form of the BA [21][22][23][24][25][26][27][28][29]. The curvature of the vessels is responsible for the difference in the assessment of the BA by these two methods.…”
Section: Plos Onementioning
confidence: 99%
“…There was an increase in the total calcium volume in the LAD, LCX and RCA by 7.6%. Coronary artery disease and cardiovascular events can be predicted using coronary artery calcium score (CACS), which is a measurement of subclinical coronary atherosclerosis [ 9 ]. Plaque regression leads to an increase in calcium volume [ 10 ].…”
Section: Discussionmentioning
confidence: 99%